Pemilihan Antara 2 Moda Feeder Kereta Cepat Jakarta Bandung dari Stasiun Padalarang - Oktavia, Tyas Eka; Naipospos, Binsar Parasian (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
This research aims to identify opportunities for modal selection between Feeder Train and Bandung Local KRD as a continuation mode for KCJB passengers from Padalarang Station to Bandung City. This research is aimed at prospective passengers of the Highspeed Railway Jakarta-Bandung (KCJB) who will later choose between the Feeder Train and the Greater Bandung Local KRD as the next mode of travel from Padalarang Station to Bandung City. The survey was carried out by distributing questionnaires online to 384 respondents and processed using the binomial logit method. It was found that based on the analysis results in BIOGEME 3.2.11, the probability attributes of cost, travel time and waiting time between trains/headway for both modes were obtained, the probability for choosing the KA Feeder is greater if the utility value is large and vice versa, the probability of selecting the KA Feeder is smaller if the utility value is small. The highest probability value for choosing the Feeder Train is 94% in scenario number 4, whereas in this scenario the probability value for the Greater Bandung Local KRD is the smallest, namely only 6%, therefore the Feeder Train Mode is a mode that has greater opportunities for the Jakarta Fast Train Bandung as an advanced mode of travel from Padalarang Station.